MATURITY AND SPAWNING OF THE SNAPPER, LUTIANUS KASMIRA (FORSKAL) FROM THE ANDAMAN SEA - Rangarajan, K (Indian Journal of Fisheries, 2011)
Lutianus kasmira of the Andaman Sea spawns only once in a year but thespawning period is likely to be spread over a period of four or five months from Novemberto March. The occurrence of mature fish over a prolonged period and high gonadosomaticindex during a number of months lend additional evidence for the prolongedspawning season of the fish. The minimum size at first maturity was about 170 mm andfifty per cent maturity was attained when the fish grew to a length of 200 mm. Fecunditywas found to fluctuate very widely from 42,100 to 332,620. The sexes were found to bedisproportionate in the catches, the males outnumbering the females, which suggests thatdifferential fishing could occur in Lutianus kasmira.